Community theatre as a site of possibility : an analysis of the role and contribution of ubuntu in transforming community theatre practitioners into cultural social agents in the Gauteng province - Radebe, Tebogo Billy (Stellenbosch : Stellenbosch University, 2025)
Thesis (DPhil)--Stellenbosch University, 2024.